Pengembangan Potensi Pariwisata Berkelanjutan Berbasis Kereta Api: Studi Kasus Relasi Kereta Api Lokal di Jawa Tengah - Wiratama, Budhi Fatanza (Jurnal Dinamika Ekonomi Pembangunan, 2025)
The end of the pandemic period has brought Central Java’s tourism sector into a phase of rapid revival. This study highlights the role of local railway networks in Central Java as a potential framework for sustainable tourism development. By combining official statistics with geospatial big data, the spatial distribution of tourist attractions and tourism infrastructure across the province was mapped using Kernel Density Estimation. In addition, a Tourism Infrastructure Spatial Index was constructed for each railway station to analyze the potential and challenges of rail-based tourism development. The findings reveal that tourism development in Central Java remains uneven. The Tourism Infrastructure Spatial Index further indicates that most railway stations are not yet connected to adequate tourism infrastructure. Nevertheless, there is considerable potential to advance rail tourism by strengthening the connectivity of strategic stations to maximize tourism impact. This study recommends the “Ring of Java” brand as an integrated rail tourism development model, mapping the connections among railway routes. It is expected that this initiative will help redistribute tourist flows from major destinations to other regions that remain underexplored.